Investigating in vitro anticancer properties of Malaysian rainforest plants: Acalypha wilkesiana Müll, Arg. Archidendron ellipticum (Blume) Hassk. Duabanga grandiflora Walp. Pseuduvaria macrophylla (Oliv.) Merr - Chu, Jessica Hoi-Yan (2014)
Malaysia is ranked the 12th richest country for its biological diversity of plant species by the Convention on Biological Diversity and this project aims to contribute to existing knowledge of Malaysian rainforest plants, Acalypha wilkesiana, Duabanga grandiflora, Archidendron ellipticum and Pseuduvaria macrophylla, for the treatment of cancer.